2006
DOI: 10.1155/2006/715459
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Breath Test for Diagnosis of Lactose Malabsorption: The Importance of Timing and the Number of Breath Samples

Abstract: Hydrogen breath test for diagnosis of lactose malabsorption: The importance of timing and the number of breath samples. Can J Gastroenterol 2006;20(4):265-268. BACKGROUND:The hydrogen breath test (H 2 BT) is the most widely used procedure in the diagnostic workup of lactose malabsorption and lactose intolerance. AIM: To establish whether a simplified two-or three-sample test may reduce time, costs and staff resources without reducing the sensitivity of the procedure. PATIENTS AND METHODS: Data from 1112 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…It should be noted that the relationship between symptom induction, and therefore intolerance rates, and malabsorption is dependent on the choice of symptom scoring, with a positive association between the number and intensity of induced symptoms and the percentage of positive hydrogen breath tests following lactose having been shown . In this study, a sensitive symptom index reflecting both intensity and symptom number was used very similar to the 9‐item validated score used by Choi et al ., with intolerance rates not greater than in other large comparative studies in Caucasians for lactose – we are not aware of any similar large studies for fructose intolerance . Only a small minority of these referred patients were able to correctly identify their food intolerance before the provocation testing, but this undoubtedly also partly reflects a referral bias to a GI practice.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It should be noted that the relationship between symptom induction, and therefore intolerance rates, and malabsorption is dependent on the choice of symptom scoring, with a positive association between the number and intensity of induced symptoms and the percentage of positive hydrogen breath tests following lactose having been shown . In this study, a sensitive symptom index reflecting both intensity and symptom number was used very similar to the 9‐item validated score used by Choi et al ., with intolerance rates not greater than in other large comparative studies in Caucasians for lactose – we are not aware of any similar large studies for fructose intolerance . Only a small minority of these referred patients were able to correctly identify their food intolerance before the provocation testing, but this undoubtedly also partly reflects a referral bias to a GI practice.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, the correlation between clinical symptoms and those experienced during breath testing is an important confirmation for the patient. A breath collection duration longer than 3 h has been recommended in previous studies for improved diagnostics of lactose intolerance …”
Section: Discussionmentioning
confidence: 99%
“…Methods used to evaluate LM include the lactose hydrogen breath test (HBT) (17)(18)(19)(20), the lactose tolerance test (LTT) (21,22), estimation of lactase concentrations in intestinal biopsy samples, and genetic tests (23). Recent studies have shown that the single nucleotide polymorphism (SNP) at position 13910 nucleotide upstream to the gene coding for lactase on chromosome-2 (LCT locus) determines the LP/LNP status (23).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study design to ours, Di Camillo et al (2006) evaluated the implications of simplifying a 4-h 30-min breath sampling lactose H 2 -BT in a large group of patients. The authors concluded that the H 2 -BT could be effectively performed with only three breath samples (0, 120 and 180 min) without a relevant loss of sensitivity (94.1%).…”
Section: Discussionmentioning
confidence: 99%